Florence Nightingale: Discernment as trusting experience - Rakoczy, Susan (HTS teologiese studies, 2018)
Discernment is a fundamental dimension of growth in the spiritual life in which the person or community analyses their experience in order to sense the call of God in their life’s trajectory. Florence Nightingale (1820–1910), the founder of modern nursing during her service in the Crimean War, discerned her call through a series of religious experiences beginning when she was 17. Her sense of vocation was met by vehement opposition from her family and others, but with the help various of spiritual advisers she was able to discern that God was calling her to serve others as a nurse when nursing was a despised occupation for women of her social class. After her return from the War, she lived a life of seclusion in order to write and organise the principles of nursing for the British Medical Service. This article presents the various dimensions of Nightingale’s vocational discernment and analyses them in reference to the feminist discernment principle of trusting one’s experience.